Strategic marketing - Cravens, David W. (McGraw-Hill, 2006)
Strategic Marketing 8/e by Cravens and Piercy is a text and casebook that discusses the concepts and processes for gaining the competitive advantage in the marketplace. The authors examine many components of a market-driven strategy, including technology, customer service, customer relationships, pricing, and the global economy. The text provides a strategic perspective and extends beyond the traditional focus on managing the marketing mix. The cases demonstrate how real companies build and implement effective strategies. Author David Cravens is well known in the marketing discipline and was the recipient of the Academy of Marketing Sciences Outstanding Marketing Educator Award. Co-author Nigel Piercy, has a particular research interest in market-led strategic change and sales management, for which he has attracted academic and practitioner acclaim in the UK and USA.